Glycerol dehydrogenation steps on Au/C surface in alkaline medium: An in-situ ATR-FTIR approach - Fontes, E. H.; Ramos, C. E.D.; Ottoni, C. A. [UNESP]; de Souza, R. F.B.; Antolini, E.; Neto, A. O. (Elsevier, 2021)
The glycerol oxidation reaction (GLYOR) was evaluated using an Au/C electrocatalyst under alkaline conditions and varying glycerol (GLY) concentration. This electrocatalyst was synthesized by the borohydride reduction method. Au/C was characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and electrochemical techniques associated with in situ attenuated total reflectance Fourier transformed infrared spectroscopy (ATR-FTIR). XRD diffractograms showed the presence of Au (fcc). Cyclic voltammetry assisted by ATR-FTIR in situ measurements revealed that GLY oxidation on gold leads to the formation of a high amount of glyceraldehyde (GLYAD) for low GLY concentrations, while a lower amount of GLYAD was observed and the formation of dihydroxyacetone (DHA) was prevalent for high GLY concentrations. For high GLY concentrations DHA is almost stable, whereas for low GLY concentration DHA is fast oxidized to hydroxypyruvate. The excellent GLYOR activity of the Au/C catalyst in low GLY concentrations leads to the formation of deeper oxidized C1 species.
Keywords: Glyceraldehyde; Glycerol oxidation reaction; Integral equation formalism for polarizable continuum model